Individual values and delinquency: on considering universals in the content and structure of values - Bilsky, Wolfgang; Hermann, Dieter (Psychology, crime & law, 2016)
The systematic relation between delinquency and the overall spectrum of individual values has not been a particular topic of psychological research in the past. To fill this gap, we refer to Schwartz’s [(1992). Universals in the content and structure of values: Theoretical advances and empirical tests in 20 countries. Advances in Experimental Social Psychology, 25, 1-65] theory of universals in the content and structure of values (TUV) and re-interpret the results of Hermann’s [(2003). Werte und Kriminalität. Wiesbaden: Springer] criminological research on individual reflexive values, norm acceptance, and self-reported delinquency against this background: We verify to what extent the Individual Reflexive Value Scale (IRVS) covers the overall spectrum of values defined by TUV. We validate this match by content analysis and multidimensional scaling (MDS) and compute IRVS-based basic and higher-order value scores. Confirmatory and spherical MDS with these scores yield the circular value structure postulated by TUV. Structural equation modelling (SEM) reveals systematic relations between basic values, norm acceptance and self-reported delinquency in accord with the ‘sinusoid curve hypothesis’. Moving around the value circle yields the highest negative correlations of self-reported delinquency with tradition and conformity and the highest positive correlations with hedonism and stimulation. These values are indicators of the higher-order value dimension ‘conservation’ versus ‘openness to change’. The significant impact of this value dimension on norm acceptance and delinquency is documented by means of SEM.